2016
DOI: 10.1007/s40258-016-0237-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost Implications for Subsequent Perinatal Outcomes After IVF Stratified by Number of Embryos Transferred: A Five Year Analysis of Vermont Data

Abstract: Attempting to improve IVF pregnancy rates by permitting multiple embryo transfers results in sharply increased rates of multiple gestation and preterm delivery. This practice yields a greater frequency of adverse perinatal outcomes and substantially increased healthcare spending. Better efforts to encourage SET are necessary to normalize healthcare expenditures considering the frequency of very high cost sequela associated with IVF where multiple embryo transfers occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…A grande maioria de estudos publicados avaliando o procedimento SET vs. DET é realizada em cenários nos quais o procedimento de fertilização in vitro não é reembolsado, visto que essa situação estimula a transferência múltipla de embriões com o objetivo de aumentar a chance de sucesso por ciclo e, consequentemente, tem o potencial de aumentar situações adversas durante a gravidez (Carpinello et al, 2016).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A grande maioria de estudos publicados avaliando o procedimento SET vs. DET é realizada em cenários nos quais o procedimento de fertilização in vitro não é reembolsado, visto que essa situação estimula a transferência múltipla de embriões com o objetivo de aumentar a chance de sucesso por ciclo e, consequentemente, tem o potencial de aumentar situações adversas durante a gravidez (Carpinello et al, 2016).…”
Section: Discussionunclassified
“…Assim, a técnica de SET sequencial (SET + SET) não só consegue minimizar a probabilidade de gravidez múltipla, quando comparada à técnica de DET, mas também tem o potencial de reduzir o risco de complicações da gestação e minimizar a chance de prematuridade extrema, baixo peso ao nascer e complicações associadas, preservando as taxas de gravidez (Cutting, 2018;Grady et al, 2012;Meldrum et al, 2018). Diversos estudos econômicos foram produzidos para estimar a custo-efetividade das técnicas de SET e DET, e o impacto econômico das gestações múltiplas no sistema de saúde (Carpinello et al, 2016;Hernandez Torres et al, 2015;Lee et al, 2016). No entanto, não há uma concordância universal sobre o tema, isso porque as análises produzidas são fortemente influenciadas pelos procedimentos médicos praticados em cada localização geográfica, tal como custo da intervenção médica e medicação necessária.…”
Section: Introductionunclassified
“…Previously published work in an Australian population where the cost of a birth admission of ART compared to non-ART population was higher, was driven by higher incidence of low birthweight and very low birthweight in that subgroup (11). Nevertheless, both the Australian population study (11) and a smaller regional US based group of patients with ART (8) included twins and higher order multiples who had incurred higher costs. Despite the large sample size, in particular in the older gestational and birthweight strata, our results do not follow the same pattern at all gestational ages.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of infant outcomes has been largely driven by prematurity and low birthweight (6, 7). Other factors are known to increase the costs for singleton offspring from ART pregnancies, including the number of embryos transferred, although the increase in costs is also largely driven by prematurity (8). Twins and higher order multiples, the numbers of which are both increased as a result of ART, are both known to contribute to increased costs compared to singletons both during the birth hospitalization and first year of life (9).…”
Section: Introductionmentioning
confidence: 99%
“…25 One study also found increased rates of preterm deliveries among singleton ART pregnancies that resulted from double or triple embryo transfer compared with single embryo transfer. 26 Another large area of interest has examined fetal and newborn size in ART offspring. A retrospective study compared all singletons conceived after FET (n ¼ 6,647) to singletons born after fresh IVF and ICSI (n ¼ 42,242) and singletons born after spontaneous conception (n ¼ 288,542) in Denmark, Norway, and Sweden.…”
Section: Assisted Reproductive Technology and Epigenetics In Humansmentioning
confidence: 99%